2008
DOI: 10.1080/00268970802275603
|View full text |Cite
|
Sign up to set email alerts
|

An MRCI investigation of the electronically excited states of difluorocarbene and its monovalent ions

Abstract: The MRCI/CBS computational protocol was employed to describe the low-lying electronic states of CF 2 in excellent agreement with experiment. Also of interest for modeling the fluorocarbon plasmas are the difluorocarbene ions, and the geometries, adiabatic excitation energies and orbital characteristics of their electronically excited states were established. Most of the transitions leading to the excited states were found to be monoelectronic and, for the dipole-allowed ones, the oscillator strengths and radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It is shown that the system moves down to crossing the corresponding PES of the N-electron system (which has its E = 0.0 value at the R eq position shown by the vertical dotted line) at a bond distance of about 1.40 Å. It is interesting to note that earlier ab initio calculations for the stable anion of 2 B 1 symmetry 37 found that its minimum energy structure was for R eq ∼1.438 Å and close to the experimental estimate of 1.45 ( 0.02 Å . 43 A smooth extrapolation of our scattering results into the bound-state region suggests a bond length of ∼1.44 Å in good agreement with the above data.…”
Section: Resonance Evolutions On Bond Deformationsmentioning
confidence: 82%
See 2 more Smart Citations
“…It is shown that the system moves down to crossing the corresponding PES of the N-electron system (which has its E = 0.0 value at the R eq position shown by the vertical dotted line) at a bond distance of about 1.40 Å. It is interesting to note that earlier ab initio calculations for the stable anion of 2 B 1 symmetry 37 found that its minimum energy structure was for R eq ∼1.438 Å and close to the experimental estimate of 1.45 ( 0.02 Å . 43 A smooth extrapolation of our scattering results into the bound-state region suggests a bond length of ∼1.44 Å in good agreement with the above data.…”
Section: Resonance Evolutions On Bond Deformationsmentioning
confidence: 82%
“…The properties of CF 2 at the equilibrium geometry were the subject of several papers from both theoretical and experimental viewpoints. The geometry of its ground state was studied spectroscopically in the microwave , and infrared , regions, and structural parameters of the ground state have been derived from absorption spectroscopy .…”
Section: Resonance Features At the Equilibrium Geometrymentioning
confidence: 99%
See 1 more Smart Citation